Wavelength selective polymer network formation of end-functional star polymers. Issue 9 (21st December 2015) - Kaupp, Michael; Hiltebrandt, Kai; Trouillet, Vanessa; Mueller, Patrick; Quick, Alexander S.; Wegener, Martin; Barner-Kowollik, Christopher
Abstract : A wavelength selective technique for light-induced network formation is introduced, combining RAFT for precursor and DLW for 3D-structure generation. Abstract : A wavelength selective technique for light-induced network formation based on two photo-active moieties, namely ortho -methylbenzaldehyde and tetrazole is introduced. The network forming species are photo-reactive star polymers generated via reversible activation fragmentation chain transfer (RAFT) polymerization, allowing the network to be based on almost any vinylic monomer. Direct laser writing (DLW) allows to form any complex three-dimensional structure based on the photo-reactive star polymers.